Selective atonal gene delivery improves balance function in a mouse model of vestibular disease - Schlecker, Christina; Praetorius, Mark; Brough, Douglas E.; Presler, R. G.; Hsu, Chi; Plinkert, Peter K.; Staecker, Hinrich (Gene therapy, 2011)
Loss of balance is often due to loss of vestibular hair cells. In mammals, regeneration of functional hair cells in the mature sensory epithelium is limited; therefore, loss of sensory cells can lead to debilitating balance problems. Delivery of the transcription factor atonal (atoh1) after aminoglycoside ototoxicity has previously been shown to induce the transdifferentiation of supporting cells into new hair cells and restore function. A problem with mouse aminoglycoside models is that the partial loss of hair cells seen in human disease is difficult to establish consistently. To more closely mirror human clinical balance dysfunction, we have used systemic application of 3,3′-iminodipropionitrile (IDPN), a vestibulotoxic nitrile compound known to cause vestibular hair cell loss, to induce a consistent partial loss of vestibular hair cells. To determine if balance function could be restored, we delivered atoh1 using a new adenovirus vector, based on Ad28. The Ad28 adenovector is based on a human serotype with a low seroprevalence that appears to target gene delivery to vestibular supporting cells. To further provide cell type selectivity of gene delivery, we expressed atoh1 using the supporting cell-specific glial fibrillary acid protein promoter. Delivery of this vector to IDPN-damaged vestibular organs resulted in a significant recovery of vestibular hair cells and restoration of balance, as measured by time on rotarod compared with untreated controls.